HIP-HOP CULTURE REPRESENTATION IN TELEVISION ADVERTISING - Kristanto Setiawan; Dyah Nurul Maliki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
This research used framing analysis by Gamson and Modigliani. This research utilized framing analysis to tell storyline of Nano-Nano Chewy Advertising. Framing Analysis by Gamson and Modigliani has been using to get hip-hop culture representative by using framing devices and reasoning devices element. This research using descriptive qualitative approach. Technique Data collecting in this research is documentation, participant passive observation, and interview. Data collecting in this research is framing analysis by Gamson and Modigliani. The result of research showing that there is an hip-hop culture representative in Nano-Nano Chewy Advertising. The representative is showing by rapping, breakdance, grafiti and fashion element. Nano-Nano Chewy Advertising have an objective to create an cool, fun, and cheeful association. This association was developed specially for Nano-Nano target market which is an teenager. This research tell that there is a functional and emotional benefit from Nano-Nano Chewy product. The Creative concept that looks cheerfull is associates with the brand tagline â€œRame Rasanyaâ€. This Advertising was create to maintain Nano-Nano top of mind brand awareness. Keyword: framing, hip-hop, representation, Advertising, Nano-Nano Chewy.